KAJIAN PUSTAKA TERHADAP OTENTISITAS AL-QUR'AN: ANALISIS HISTORIOGRAFI PROSES KODIFIKASI MUSHAF - Sarmin; Muhammad Tajuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study comprehensively examines the codification process of the Qurʼān from the period of revelation to the establishment of the Uthmanic standard mushaf. Employing a historical-critical approach with a descriptive-analytical method, this research traces four main phases of codification: memorization and writing during the Prophet Muhammad’s time, the first compilation of the mushaf under Abu Bakr al-Siddiq, the standardization of the mushaf by Caliph Uthman ibn Affan, and the refinement of rasm and vocalization marks in the tabiʼin era. The findings demonstrate that the Qurʼanic codification process was systematic, gradual, and governed by rigorous principles ensuring the authenticity of the sacred text. The implications of this study affirm that the Qurʼān in circulation today constitutes an authentic transmission of the original text received by the Prophet.